Cardiovascular Action of Insulin in Health and Disease: Endothelial L-Arginine Transport and Cardiac Voltage-Dependent Potassium Channels - Dubó, Sebastián; Gallegos, David; Cabrera, Lissette; Sobrevia, Luis; Zúñiga, Leandro; González, Marcelo (Frontiers in Physiology, 2016)
The impairment of insulin signaling on diabetes mellitus has been related to cardiovascular dysfunction, heart failure and sudden death. In human endothelium, cationic amino acid transporter 1 (hCAT-1) is related to the synthesis of nitric oxide (NO). Insulin has a vascular effect in endothelial cells through a signaling pathway that involved increases of hCAT-1 expression and L-arginine transport. This mechanism is disrupted in diabetes, a phenomenon potentiated by excessive accumulation of reactive oxygen species (ROS), which contributes to lower availability of NO and endothelial dysfunction. On the other hand, the electrical remodeling in cardiomyocytes is considered a key factor in heart failure progression associated to diabetes mellitus, generating a challenge to understand the specific role of insulin and the pathways involved in cardiac function. Studies on isolated mammalian cardiomyocytes have shown a prolongated action potential in ventricular repolarization phase that produces a long QT interval. The long QT generated is well explained by attenuation in the repolarizing potassium currents in cardiac ventricles. The impaired insulin signaling causes specific changes in these currents, such a decrease amplitude of the transient outward K+ (Ito) and the ultra-rapid delayed rectifier (IKur) currents where, together, a reduction of mRNA and protein expression levels of α-subunits (Ito, fast; Kv 4.2 and IKs; Kv 1.5) or β-subunits (KChIP2 and MiRP) of K+ channels involved in these currents in a MAPK mediated pathway process have been described. These results support the hypothesis that the lack of insulin signaling can produce an abnormal repolarization in cardiomyocytes. Furthermore, the arrhythmogenic potential due to reduced Ito current can contribute to an increase in the incidence of sudden death in heart failure. This review aims to show, based on pathophysiological models, the regulatory function that would have insulin in vascular system and in cardiac electrophysiology.